A quantitative transcriptomic analysis of the physiological significance of mTOR signaling in goat fetal fibroblasts. (December 2016) - Fu, Yuting; Zheng, Xu; Jia, Xiaoyang; Binderiya, Uyanga; Wang, Yanfeng; Bao, Wenlei; Bao, Lili; Zhao, Keyu; Fu, Yu; Hao, Huifang; Wang, Zhigang
Abstract Background Mammalian target of rapamycin (mTOR) is an evolutionarily conserved serine/threonine kinase that is a central regulator of cell growth and metabolism. CCI-779 is a specific inhibitor of the mTORC1 signaling pathway. Results We performed comparative transcriptome profiling on Inner Mongolia Cashmere goat fetal fibroblasts (GFbs) that were treated with CCI-779 and untreated cells. A total of 365 differentially expressed genes (DEGs) appeared between untreated and CCI-779-treated GFbs, with an FDR ≤0.001 and fold-change ≥2. These 365 DEGs were associated with mTOR signaling; 144 were upregulated in CCI-779-treated cells, and 221 were downregulated. Additionally, 300 genes were annotated with 43 Gene Ontology (GO) terms, and 293 genes were annotated with 194 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Three RNA polymerase II and polymerase III subunits, 3 transcription factors, and 5 kinases in mTOR signaling were differentially expressed in CCI-779-treated GFbs. Further 6 DEGs were related to amino acid metabolism, 11 mediated lipid metabolism, 11 participated in carbohydrate metabolism, and 5 were involved in single-nucleotide metabolism. Based on our quantitative transcriptomic analysis, 40 significant DEGs with important function related to metabolism, RNA polymerase, transcription factors and mTOR signaling were selected for qPCR analysis, and the quantitative results between the two analysis methods were concordant. The qPCR data confirmed the differential expression in the RNA-Seq experiments. To validate the translational significance of the findings in certain differentially expressed genes, S6K1 and VEGF were detected by western blot, and these two proteins showed a differential expression between non-treated and treated with CCI-779 groups, which were consistent with mRNA abundance. The data showed a preliminary significance of the findings in the protein levels. Conclusions CCI-779 induces transcriptomic changes, and mTOR signaling might have significant function in the activation of RNA polymerase and certain transcription factors and in the metabolism of amino acids, lipids, carbohydrates, and single nucleotides in GFbs. These data filled the vacancy in the systematical profiling of mTOR signaling on Cashmere goat fetal fibroblasts.